Risk of Escherichia coli O157:H7 infection linked to the consumption of beef - Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari; New, Chia Yeung; Anyi, Ubong; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Rynnye Lyan Resources, 2017)
Escherichia coli O157:H7 is a major food-borne pathogen that has resulted in numerous outbreaks around the world. Widespread distribution of the organism in various ecological niches impedes the control measures. This study aimed to detect and quantify E. coli O157:H7 in beef sold in wet markets and hypermarkets in Malaysia and to determine the risk of E. coli O157:H7 infection linked to consumption of beef. The rfb O157 and flicH7 primers targeted on somatic antigen (O157) and flagellar antigen (H7) respectively of E. coli O157:H7 was used for the MPN-PCR method. A total of 99 beef samples were collected from local wet markets and hypermarkets. The highest E. coli O157:H7 contamination rate was observed in beef samples collected from wet markets (89.50%), whereas the contamination rate in hyper market A and B were compratively low (35.35 and 20% respectively). However, the microbial load was highest in the beef samples from hypermarket A (1100 MPN/g) while E. coli O157:H7 bacterial load in beef samples from hypermarket B and wet market ranged from 3 to 93 MPN/g and 3 to 240 MPN/g, respectively. Using the Quantitative Microbial Risk Assessment (QMRA) approach the risk was estimated incorporating the findings of the prevalence study and predictions based on home storage, cooking and consumption patterns. Three different exposure pathways were investigated to estimate the risk associated with contaminated beef and Monte Carlo simulation was used to determine the level of uncertainty. The developed model predicated that consumption of contaminated beef can be accountable for 1.83E+06 E. coli O157:H7 cases per year in Malaysia. The reliability of the model, data gaps and further research needs, is discussed. Through continuous improvement Quantitative Microbial Risk Assessment provides valuable insight into controlling and prevention strategies.